2020
DOI: 10.1061/(asce)gt.1943-5606.0002251
|View full text |Cite
|
Sign up to set email alerts
|

Drained Seismic Compression of Unsaturated Sand

Abstract: Seismic compression of unsaturated soils occurs due to particle rearrangement during largestrain cyclic shearing which may be resisted by interparticle stresses that depend on the matric suction and degree of saturation. Due to the high rate of shearing in earthquakes, seismic compression is expected to be an undrained phenomenon with changes in total volume, matric suction, and degree of saturation along with an evolution in soil hydro-mechanical properties during cyclic shearing. To simplify this problem and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In the drained cyclic simple shear tests of Rong and McCartney (2020), the seismic compression of unsaturated sands in the funicular regime after a large number of cycles was observed to have a log-linear relation with matric suction from the values observed for unsaturated sand. For smaller numbers of cycles (i.e., 200 cycles), they found that specimens with an initial degree of saturation of 0.1 had the lowest seismic compression.…”
Section: Cyclic Volumetric Behavior Of Unsaturated Soilsmentioning
confidence: 84%
See 4 more Smart Citations
“…In the drained cyclic simple shear tests of Rong and McCartney (2020), the seismic compression of unsaturated sands in the funicular regime after a large number of cycles was observed to have a log-linear relation with matric suction from the values observed for unsaturated sand. For smaller numbers of cycles (i.e., 200 cycles), they found that specimens with an initial degree of saturation of 0.1 had the lowest seismic compression.…”
Section: Cyclic Volumetric Behavior Of Unsaturated Soilsmentioning
confidence: 84%
“…Although partial drainage was observed in the centrifuge shaking table tests on unsaturated sand layers reported by Ghayoomi et al (2011Ghayoomi et al ( , 2013, the trends 6 in seismic compression with degree of saturation were similar to those reported in these previous studies on drained conditions. However, direct comparisons in trends are difficult as the cyclic shear strain amplitudes in these studies are all different, ranging from values on the order of 0.06% in Le and Ghayoomi (2017) to values on the order of 5% in Rong and McCartney (2020).…”
Section: Cyclic Volumetric Behavior Of Unsaturated Soilsmentioning
confidence: 96%
See 3 more Smart Citations